Client–server architecture for collaborative remote experimentation - Callaghan, M.J.; Harkin, J.; McColgan, E.; McGinnity, T.M.; Maguire, L.P. (Journal of network and computer applications, 2007)
Experience in teaching engineering related subjects has shown that a complementary approach combining theoretical and practical exercises is vital for effective learning. Increasingly, teaching institutions are offering remote access to distant laboratories as part of an overall e-learning strategy. However, the majority of remote access laboratories developed to date have suffered from a major deficiency, namely the provision of a web-based environment that accurately recreates the group working and tutor driven experience of traditional on-campus based laboratories. This paper addresses this issue and presents a client–server architecture, based on Web services and .NET remoting services, for an integrated learning environment for remote experimentation that allows students in disparate locations to simultaneously and collaboratively complete complex experimental exercises.